2011
DOI: 10.1007/s00894-011-1200-7
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes in 2-trans-enoyl-ACP (CoA) reductase (InhA) from M. tuberculosis induced by an inorganic complex: a molecular dynamics simulation study

Abstract: InhA, the NADH-dependent 2-trans-enoyl-ACP reductase enzyme from Mycobacterium tuberculosis (MTB), is involved in the biosynthesis of mycolic acids, the hallmark of mycobacterial cell wall. InhA has been shown to be the primary target of isoniazid (INH), one of the oldest synthetic antitubercular drugs. INH is a prodrug which is biologically activated by the MTB catalase-peroxidase KatG enzyme. The activation reaction promotes the formation of an isonicotinyl-NAD adduct which inhibits the InhA enzyme, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…These include analysis of molecular complex formation and stability [Monecke et al, 2013; Norberto de Souza and Ornstein, 1999], predictions of enzyme-substrate activity [Chien et al, 2012], effects of mutations on drug resistance [Schroeder et al, 2005], and inhibitor binding [Costa et al, 2012]. …”
Section: Resultsmentioning
confidence: 99%
“…These include analysis of molecular complex formation and stability [Monecke et al, 2013; Norberto de Souza and Ornstein, 1999], predictions of enzyme-substrate activity [Chien et al, 2012], effects of mutations on drug resistance [Schroeder et al, 2005], and inhibitor binding [Costa et al, 2012]. …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, molecular docking calculations have also suggested that IQG607 can bind directly and reversibly to InhA [53]. These data were the only mechanistic pieces of information regarding IQG607 action until now.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, application of molecular dynamics to investigate internal motions and biological functions of biomacromolecules has opened new frontiers. Vast amounts of information on molecular recognition and binding [68][69][70][71], conformations or conformational changes [72][73][74][75], molecular mechanisms of bioactivity and stability [76][77][78][79], and drug discovery [80][81][82][83][84] have been found. To understand interaction of drugs with proteins or DNA, consideration should be given not only to the static structures but dynamical information obtained by simulation through a dynamic process.…”
Section: Author Summarymentioning
confidence: 99%